Purification of single-walled carbon nanotubes - Yaya, A.; Ewels, C.; Wagner, Ph.; Suarez-Martinez, Irene; Tekley, G.; Jensen, L.R. (Cambridge University Press, 2011)
We present a study of purification of single-walled carbon nanotubes (SWCNTs) using different oxidation temperatures and chemical treatments. We have developed a simple two annealing-steps procedure resulting in high nanotube purity with minimal sample loss. The process involves annealing the SWCNTs at 300˚C for 2 h with subsequent reflux in 6 M HCl at 130˚C, followed by further annealing at 350˚C for 1 h with reflux in 6 M HCl at 130˚C. The process results in effective removal of carbon impurities and metal particles which are associated with SWCNTs production. The process is less time-consuming (complete in 4.5 h) than conventional acid purification methods which require over 5 h, and less destructive than conventional methods with a yield of 26%. SWCNT purity was assessed using Raman spectroscopy, thermogravimetry and scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy.